Intestinal streaming patterns in cholerrhoeic enteropathy and diverticular disease. Issue 3 (March 1974) - Findlay, J. M.; Mitchell, W. D.; Eastwood, M. A.; Anderson, A. J. B.; Smith, A. N.
Abstract : Streaming of gastrointestinal contents depends on the demonstration of differential rates of recovery of equal doses of two synchronously fed markers. There was no significant difference in the rate of throughput of polyethylene glycol (a liquid phase marker) and chromium sesquioxide (a solid phase marker) in healthy volunteers (n = 7) and hospital inpatients (n = 5) with normal bowel habit, so that streaming does not usually occur. In cholerrhoeic enteropathy (n = 5), however, the rate of throughput of polyethylene glycol was increased. In colonic diverticular disease (n = 7) the rate of throughput of polyethylene glycol was significantly lower. In cholerrhoeic enteropathy the liquid phase marker was excreted 1·5 times faster than the solid phase, but in the diverticular disease group the liquid phase was excreted 0·75 times more slowly than the solid phase marker. This may reflect the effects of colonic hypersegmentation on the relative distribution of the liquid and solid phases.